Toxins Produced by Fusarium Species in Leaf Scorch Decline Affected Coconut Palms (Cocos nucifera L.): Quantitative Analysis of Fusaric Acid, Zearalenone and T-2 - P. H. A. P Siriwardhana; L. C. P. Fernando; J. M. M. A. Jayasundara (International Coconut Community, 2009)
Leaf Scorch Decline (LSD) is a disorder of coconut (Cocos nucifera L.) prevalent in Sri Lanka, for which the etiology is yet unknown and hence a study was conducted to identify the toxins produced by Fusarium spp. associated with LSD-affected palms. Root, stem and leaf tissues of LSD-affected and healthy palms were used to analyze the toxin content. Gas Chromatographic (GC) analysis carried out for Fusaric acid (FA), Zearalenone (ZEA) and T-2 (a Trichothecene) revealed the presence of FA in stem or leaves of many affected palms, but not in any of the roots. Total FA in stem and leaves was significantly higher (p>0.01) in affected palms than in healthy palms. Healthy palms were free of FA. Although ZEA and T-2 were present in both healthy and affected palms, the only significant difference between the two groups was ZEA in stem tissues. A strong association between FA and the presence of ZEA suggest they influence the production of LSD symptoms. The similarity of symptoms of Fusarium wilt diseases in other plants and LSD are discussed.